2014
DOI: 10.1542/peds.2014-1282
|View full text |Cite
|
Sign up to set email alerts
|

Pediatricians' Communication About Weight With Overweight Latino Children and Their Parents

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Little is known about how pediatricians communicate with overweight Latino children and their parents regarding overweight and obesity.WHAT THIS STUDY ADDS: Findings suggest that many overweight Latino children and their parents do not receive direct communication that the child is overweight, weight-management plans, culturally relevant dietary recommendations, or follow-up visits. RESULTS:The mean child age (N = 26) was 9.5 years old; 81% were obese. Sixty-two percent of parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The lived experience literature recommended that HCPs should ensure that their communication (verbal and non‐verbal) conveys respect, trust, openness and sensitivity to cultural values . Some authors suggested that HCPs use parents’ non‐verbal cues (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lived experience literature recommended that HCPs should ensure that their communication (verbal and non‐verbal) conveys respect, trust, openness and sensitivity to cultural values . Some authors suggested that HCPs use parents’ non‐verbal cues (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Both parents and HCPs recommended using communication tools, such as growth charts, pictures and handouts as a non‐judgmental way to facilitate conversations about a child's weight status , although the exact nature of the tools varied. Such visual tools were especially recommended when a HCP is not fluent in the client/family's native language . Using tools may also help HCPs provide a rationale for the changes in behaviour that they are recommending , e.g.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, only one study has examined the healthcare provider communication experiences of parents of minority children with obesity during weight management conversations. This study, conducted among Latino parents, found that pediatricians frequently use stigmatizing terms like “fat” to describe the child’s body and rarely discuss culturally relevant dietary recommendations [31]. …”
Section: Introductionmentioning
confidence: 99%
“…Childhood obesity is strongly associated with multiple comorbid problems, such as high blood pressure, hyperlipidemia, dysglycemia, poor health status, and emotional/behavioral problems 9-10,12 ; however, rates of risk-factor screening and communication appear to be suboptimal, according to data from a cross-sectional study of video-recorded provider-patient communication regarding weight-management: providers discussed family history in 35% of visits, communicated abnormal physical-exam findings in 42% of visits, and recommended obesity-related laboratory studies in 62% of visits. 13 The study findings suggest that performing risk-factor screening and result communication may help providers partner with parents and overweight children on weight management.…”
Section: Discussionmentioning
confidence: 87%